2016
DOI: 10.1016/j.elecom.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of a single nanochannel investigated by high-frequency impedance spectroscopy

Abstract: The high frequency electric impedance spectroscopy is used to characterize the dielectric properties of a single nanochannel in a micro/nanofluidic device. The simulated electric impedance results lead to the determination of two conductance regimes, a non ideal capacitance and its surface charge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…After Ce-doped, the time constant was decreased (τ = 1/ω*), indicating fast surface redox reaction. 25,26 According to the above results, we concluded that Ce-doped MnO 2 not only increased the specific capacitance but also optimized the electron and ion transfer/diffusion.…”
Section: ■ Introductionmentioning
confidence: 73%
“…After Ce-doped, the time constant was decreased (τ = 1/ω*), indicating fast surface redox reaction. 25,26 According to the above results, we concluded that Ce-doped MnO 2 not only increased the specific capacitance but also optimized the electron and ion transfer/diffusion.…”
Section: ■ Introductionmentioning
confidence: 73%
“…As the height of the nanochannel, hn, is very small (a hundred nanometers), the EDL thickness may become not negligible and affects the total conductance. Indeed, if λD < h/2, the nanochannel conductance [29], [34], [36], is governed by its bulk conductance expression defined as follows,…”
Section: The Simplified Nanochannel Conductance Modelmentioning
confidence: 99%
“…Indeed, as we mentionned previously, several studies already exist on nanochannel conductance but they either involve even unique nanochannel length due to long micro nanofabrication process or time consuming for an experimental characterization [34]. It thus should be interesting to investigate the role played by the nanochannel length and its connected microchannels to contribute on the improvement of the models for conductance laws proposed in the literature.…”
Section: Introductionmentioning
confidence: 98%
“…The frequency range used for HFEIS measurements was varied from 10 MHz to 1 Hz. The sinusoidal AC signal excitation between Ag|AgCl wires is set to 100 mV peak to peak since DC was fixed to 0 V. 40 Experimental Protocols. To measure the global MNM conductance, the procedure described below was followed for various concentrations of the supporting electrolyte.…”
Section: ■ Introductionmentioning
confidence: 99%